Wal-Mart : the store wars - Diermeier, Daniel ([London] : SAGE, 2016)
In early 2004, residents of Inglewood, California voted on a referendum that would change the city charter to allow Wal-Mart to build a supercentre on a huge, undeveloped lot in the city. Wal-Mart had put forward the measure after the city council refused to change the zoning of a plot on which it held an option to build. Numerous community and religious groups opposed Wal-Mart's entry and campaigned against the referendum. Walmart promised low-priced merchandise and jobs, but these groups were skeptical about the kinds of jobs and compensation that would be offered. This case examines the divisive issues.
Originally Published in: Diermeier, D. (2011). Wal-Mart: The Store Wars. 5-406-751. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Wal-Mart (Firm); Social responsibility of business -- Case studies; Strategic planning -- Case studies; Crisis management -- Case studies